Nondeterministic nature of sensorineural outcomes following noise trauma - O'neil W. Guthrie; Ishan S. Bhatt (Biology Open, 2021)
Over 1.1 billion individuals are at risk for noise induced hearing loss yet there is no accepted therapy. A long history of research has demonstrated that excessive noise exposure will kill outer hair cells (OHCs). Such observations have fueled the notion that dead OHCs underlie hearing loss. Therefore, previous and current therapeutic approaches are based on preventing the loss of OHCs. However, the relationship between OHC loss and hearing loss is at best a modest correlation. This suggests that in addition to the death of OHCs, other mechanisms may regulate the type and degree of hearing loss. In the current study, we tested the hypothesis that permanent noise-induced-hearing loss is consequent to additional mechanisms beyond the noise dose and the death of OHCs. Hooded male rats were randomly divided into noise and control groups. Morphological and physiological assessments were conducted on both groups. The combined results suggest that beyond OHC loss, the surviving cochlear elements shape sensorineural outcomes, which can be nondeterministic. These findings provide the basis for individualized ototherapeutics that manipulate surviving cellular elements in order to bias cochlear function towards normal hearing even in the presence of dead OHCs.